PRODUKTIVITAS KERJA PADA PELAYANAN TIKET DI PT. PELNI SORONG DENGAN METODE STOPWATCH TIME STUDY - Masniar Masniar; Ashar Ashar; Orgenes Paulus Atanay (Metode : Jurnal Teknik Industri, 2022)
Measurement of work productivity or work measurement is an attempt to determine the length of work required by an operator or worker in completing a specific job at a normal work speed level in the best work environment at that time. As a national company PT. Pelni is always required to provide good service. For this reason, it is necessary to know the standard of service time for PT. Pelni Sorong branch and measuring employee productivity. In this study, we use a Stopwatch Time Study to collect the data needed to meet the needs of the work sampling calculation process. After doing the research, the total standard time is obtained as follows: (1) for employee 1 on day 1 which is 390,225 seconds or 6,504 minutes (2) for employee 2 on day 1 which is 390,590 seconds or 6,526 minutes (3) for employee 1 on day 2 which is 388,366 seconds or 6,473 minutes (4) for employee 2 on day 2 which is 402.87 seconds or 6,715 minutes, each to serve 1 ticket purchase. The calculation results show the level of work productivity as follows: (1) on employee 1 on day 1 it reaches 77% (2) on employee 2 on day 1 of 68% (3) on employee 1 on day 2 of 68% (4) on employee 2 on day 2 by 67%.